GAMBARAN PELAKSANAAN PMTCT DI RSUD DR. MOEWARDI SURAKARTA - Prasetyo, Budi (Journal of Advanced Nursing and Health Sciences, 2020)
HIV infection is a major health problem and an infectious disease that can affect maternal and child mortality. The hospital is the spearhead of the implementation of PMTCT, especially Prong III, which is the prevention of HIV transmission from HIV positive pregnant women to their babies. The purpose of this study was to explore the implementation of PMTCT in RSUD Dr. Moewardi Surakarta. The research was conducted using a qualitative research method with a case study design to collect in-depth information about how patients experience and behavior in participating in the PMTCT program. The main informants in this study were PLWHA who had / are currently receiving PMTCT services at RSUD Dr. Moewardi, totaling 6 people. Cross check informants were counselors, case managers, pediatricians, obstetricians, as well as VCT clinical administration staff at RSUD Dr. Moewardi who participated in the PMTCT program. The results showed that the implementation of PMTCT in RSUD Dr. Moewardi can run well according to the PMTCT guidelines from the Indonesian Ministry of Health. The experience of health workers in managing the PMTCT program and the integration of the program into several child polyclinics and Ponek made PMTCT services run well and received support from all health workers related to PMTCT services.